UUM first university to adopt QR Code application - Borneo Post, (KK) (Borneo Post, 2015)
ALOR SETAR: Universiti Utara Malaysia (UUM) will be the first university to adopt the QR Code (Quick Response Code) reader application to check on graduates' data through smartphone access.